Degree of Biomimicry of Artificial Spider Silk Spinning Assessed by NMR Spectroscopy. Issue 41 (30th August 2017) - Otikovs, Martins; Andersson, Marlene; Jia, Qiupin; Nordling, Kerstin; Meng, Qing; Andreas, Loren B.; Pintacuda, Guido; Johansson, Jan; Rising, Anna; Jaudzems, Kristaps
Abstract: Biomimetic spinning of artificial spider silk requires that the terminal domains of designed minispidroins undergo specific structural changes in concert with the β‐sheet conversion of the repetitive region. Herein, we combine solution and solid‐state NMR methods to probe domain‐specific structural changes in the NT2RepCT minispidroin, which allows us to assess the degree of biomimicry of artificial silk spinning. In addition, we show that the structural effects of post‐spinning procedures can be examined. By studying the impact of NT2RepCT fiber drying, we observed a reversible beta‐to‐alpha conversion. We think that this approach will be useful for guiding the optimization of artificial spider silk fibers. Abstract : Focus on spider silk terminal domains as reporters for biomimicry: By combining solution and solid‐state NMR methods, structural changes of the terminal domains in a designed spider silk protein (NT2RepCT) are monitored in addition to the β‐sheet conversion of the central repetitive region, thereby providing an assessment of biomimicry of the fiber spinning process.